The Effect of Subclinical Hypothyroidism on Coagulation and fibrinolysis: A Systematic Review and Meta-Analysis - Xu, Qinglei; Wang, Yulong; Shen, Xue; Zhang, Yunfeng; Fan, Qingyun; Zhang, Wei (Frontiers in Endocrinology, 2022)
Background: Despite patients with thyroid dysfunction show obvious abnormal hemostatic indicators in the peripheral blood, the current research on whether and how subclinical hypothyroidism (SCH) influence hemostatic function (the coagulation and fibrinolytic system) still remains controversial. Objective: We conducted this study to evaluate how SCH influence on the coagulation and fibrinolytic system in human body. Methods: Prior to March 2022, Web of Science, Embase, PubMed, WanFang, CNKI data and reference lists were searched to identify eligible researches. Two of us independently extracted the data and evaluated study quality. The effect size is represented by standard mean difference (SMD). Both fixed and random-effects models were used where appropriate. Review Manager 5.3 and STATA 16.0 were used to analyze the eligible data.. Results: 1325 patients from twelve observational studies were involved in our research. Our study revealed that SCH changed the heamostatic balance towards hypercoagulable and hypofibrinolytic conditions accompanied by an increase in tissue fibrinogen, plasminogen activator and plasminogen activator inhibitor-1. By contrast, there was no statistically difference in acivated partial thromboplastin time (APTT) and D-Dimer in SCH group compared with that in control subjects. Conclusions: Our study confirmed that SCH is related with a prothrombotic state, as reflected by changes in both coagulation and fibrinolysis. It is highly recommended for screening cardiovascular risk factors in combination with an adequate evaluation of SCH state.